Stem-Loop Structures within mRNA Coding Sequences Activate Translation Initiation and Mediate Control by Small Regulatory RNAs - Jagodnik, Jonathan; Chiaruttini, Claude; Guillier, Maude (Molecular cell, 2017)
Initiation is the rate-limiting step of translation, and in bacteria, mRNA secondary structure has been extensively reported as limiting the efficiency of translation by occluding the ribosome-binding site. In striking contrast with this inhibitory effect, we report here that stem-loop structures located within coding sequences instead activate translation initiation of the Escherichia coli fepA and bamA mRNAs involved in iron acquisition and outer membrane proteins assembly, respectively. Both structures promote ribosome binding in vitro, independently of their nucleotide sequence. Moreover, two small regulatory RNAs, OmrA and OmrB, base pair to and most likely disrupt the fepA stem-loop structure, thereby repressing FepA synthesis. By expanding our understanding of how mRNA cis-acting elements regulate translation, these data challenge the widespread view of mRNA secondary structures as translation inhibitors and show that translation-activating elements embedded in coding sequences can be targeted by small RNAs to inhibit gene expression.